CONDITIONS OF STRESS WAVE FORMATION DURING BLASTING OF BOREHOLE CHARGES AND THEIR INFLUENCE ON ROCK FRACTURE QUALITY - Yuriy A. Masaev; Vladislav Yu. Masaev; Yuriy V. Drozdenko; Olesya Y. Aksenova (Известия Томского политехнического университета: Инжиниринг георесурсов, 2021)
The relevance. Explosive mining requires destroying rocks that lie at different depths in different mining and geological conditions and have different physical and technical properties. Explosion of explosive blast charges generates stress waves and pressure of explosion products, which have different effects on rocks of different hardness and to improve their action, explosive blast charges must be blasted with different deceleration. The main aim of the research is to take into account the energy characteristics of explosives, the position of borehole charges relative to the natural fracturing of the rock to improve the quality of fracture of blasted rock. Objects: underground construction facilities, coal and ore mines, mining enterprises for open-pit and underground mining. Methods. To achieve this goal, we used field studies to establish the dependence of rock fracture quality on the operating time of bore charges, as well as analytical studies that allowed us to determine the values of the limiting radii of expansion of the charge cavity for some types of explosives. Results. The results of the research are a more complete accounting of energy characteristics of explosives, the optimal volumetric position of borehole charges in relation to systems of natural fracturing of the environment, their correlation with the hardness of rocks, the cross section of mine workings and the depth of placing explosives charges, leading to creation of rational volumes of cuts, providing the highest performance blasting operations.